Using machine learning to advance synthesis and use of conservation and environmental evidence. Issue 4 (10th July 2018) - Cheng, S.H.; Augustin, C.; Bethel, A.; Gill, D.; Anzaroot, S.; Brun, J.; DeWilde, B.; Minnich, R.C.; Garside, R.; Masuda, Y.J.; Miller, D.C.; Wilkie, D.; et al.
Abstract : Article impact statement : Machine learning optimizes processes of systematic evidence synthesis and improves its utility for evidence‐based conservation.